2022
DOI: 10.1111/dom.14774
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and osteoporosis: A potential association with therapeutic implications

Abstract: Nonalcoholic fatty liver disease (NAFLD) and osteoporosis are two highly prevalent metabolic diseases. Increasing experimental evidence supports a pathophysiological link between NAFLD and osteoporosis. A key feature could be chronic, low‐grade inflammation, which characterizes NAFLD and possibly affects bone metabolism. In this context, several factors, including but not limited to receptor activator of nuclear factor kappa‐B ligand, osteoprotegerin, osteopontin and osteocalcin, may serve as mediators. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 134 publications
(294 reference statements)
0
10
0
1
Order By: Relevance
“… 94 However, data from clinical studies currently remain controversial, as elsewhere summarized in detail. 95 Regarding cardiovascular safety, which is a major concern for patients with NAFLD, since cardiovascular diseases represent the first cause of death of NAFLD patients, 86 there are limited data reporting an increase in heart rate and blood pressure after treatment with some FGF-21 analogs, which, however, were not shown by other authors. 96 , 97 The clinical significance of these cardiovascular effects remains to be shown, as well as whether these effects outweigh the above mentioned beneficial effect of FGF-21 analogs on lipid profile, in terms of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“… 94 However, data from clinical studies currently remain controversial, as elsewhere summarized in detail. 95 Regarding cardiovascular safety, which is a major concern for patients with NAFLD, since cardiovascular diseases represent the first cause of death of NAFLD patients, 86 there are limited data reporting an increase in heart rate and blood pressure after treatment with some FGF-21 analogs, which, however, were not shown by other authors. 96 , 97 The clinical significance of these cardiovascular effects remains to be shown, as well as whether these effects outweigh the above mentioned beneficial effect of FGF-21 analogs on lipid profile, in terms of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Partial evidence reported that RANKL upregulation could play a key role in NAFLD pathogenesis and be the possible link between hepatic and bone impairment, so its downregulation could be protective for liver health (and bone, too) [ 303 , 304 ]. A suggestive paper reported amelioration of liver function in a woman with NASH and osteoporosis after denosumab administration [ 305 ].…”
Section: Bone Density Defectsmentioning
confidence: 99%
“…Conversely, as an endocrine organ, bones secret bonederived factors that regulate local bone metabolism and systemic energy metabolic functions. Osteopontin (OPN), irisin, osteocalcin (OCN), and osteoprotegerin (OPG) probably mediate the interactions between bones, adipose tissues, and the liver 7 . Bone-derived factors including OPN and OCN play a role in NAFLD development 8 .…”
Section: Introductionmentioning
confidence: 99%